Seleksi beberapa isolat Pseudomonas kelompok Fluorescens yang berpotensi mengendalikan Fusarium oxysporum f. sp. lycopersici penyebab layu tomat secara in vitro - Hesron Induek; Derek Kornelis Erari; Adelin Elsina Tanati; Yacob Bodang (Agrotek, 2020)
This study aimed to determine the potential of several isolates of Pseudomonas fluorescens group from the rhizosphere as biological agents in suppressing the growth of F. oxysporum f.sp. lycopersici in vitro. The method used in this research is an experimental method, by selecting several isolates of Pseudomonas bacteria group fluorescens that have the potential to control the pathogen F. oxysporum in vitro. The results showed that Pseudomonas isolates from fluorescens groups M1, M2, M3, and M4 had the potential to control the pathogen F. oxysporum f.sp. lycopersici in vitro by inhibiting the growth of pathogens. The average percentage of pathogen growth inhibition from the highest was isolate M2 (64.18%), isolate M3 (62.53%), isolate M1 (60.02%), and isolate M4 (60%).